1997
DOI: 10.1136/thx.52.10.879
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcome measures for patients with chronic obstructive pulmonary disease (COPD) in an outpatient setting.

Abstract: Evidence from this study supports the CRQ and the SF-36 as comprehensive outcome measures for patients with longstanding COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
119
3
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(139 citation statements)
references
References 15 publications
11
119
3
6
Order By: Relevance
“…We also demonstrated that health status instruments can provide additional information to supplement the other clinical and physiological measures used in clinical research. The results of our study, in terms of reliability, validity and responsiveness, did not clearly favour one instrument over another, as previously shown in other studies (28,33,34). As expected, the symptoms dimension domain of the SGRQ cannot be used to assess acute changes from a given therapy.…”
Section: Resultssupporting
confidence: 67%
“…We also demonstrated that health status instruments can provide additional information to supplement the other clinical and physiological measures used in clinical research. The results of our study, in terms of reliability, validity and responsiveness, did not clearly favour one instrument over another, as previously shown in other studies (28,33,34). As expected, the symptoms dimension domain of the SGRQ cannot be used to assess acute changes from a given therapy.…”
Section: Resultssupporting
confidence: 67%
“…While differences between this economic subsample and the full sample are not statistically significant, we are limited in our ability to detect differences between the two arms due to the smaller sample size. This problem is perhaps compounded by the possible insensitivity of the EQ-5D seen in several studies (Harper et al, 1997;Nicholl et al, 2001;Patel et al, 2004). Taken together, the lack of a clear pattern in the QALY estimates shown in Table 5 is difficult to interpret.…”
Section: Discussionmentioning
confidence: 49%
“…However, Professor Dowie seems sceptical as to the empirical evidence regarding the sensitivity of CSMs over generics. We agree there are cases that do not support this common claim in the psychometric literature [3], but equally there are many where this has been found including: EQ-5D in chronic pulmonary disease [4] and in cosmetic surgery [5], the SF-36 in urinary incontinence [6] and the example of urinary incontinence that he provides [7]. Copyright The main concern people have with generic measures is that their domains are too far removed from those of the patient and are often irrelevant to the condition.…”
mentioning
confidence: 79%